Health promotion trials at worksites and risk factors for cancer - Janer, Gemma; Sala, Maria; Kogevinas, Manolis (Scandinavian Journal of Work, Environment & Health, 2002)
Studies of worksite health promotion have frequently reported larger effects than those at the community level. Many of these studies have serious methodological problems. Forty-five worksite health promotion trials following specific quality criteria were selected and estimated for behavioral changes in cancer risk factors and the effectiveness of different intervention components. Tobacco control programs found quit rates of about 5% with relapse rates of 40% to 80% at 6 months after the intervention. Effectiveness increased with the duration of the intervention for at least 6 months, repeated contacts with the participants, continuous support, and tailored messages. There was less evidence for the long-term effectiveness of incentives. Trials on diet, alcohol, physical activity, overweight, and solar radiation showed the same positive trends. The overall evidence indicates a modest but positive effect of health promotion trials at worksites and the effect, for smoking cessation trials, is slightly larger than that of community-based trials. Many of the recommendations made to increase participation and effectiveness were not based on empirical data.
Keywords: alcohol; cancer; cancer prevention; diet; health behavior; health promotion; intervention trial; obesity; physical activity; review; risk factor; tobacco; worksite